Abuse recognition by shelter staff and shelter animal adopters - Ineke R. van Herwijnen; Nadieh Reinders; Esmee M. Bus; Claudia M. Vinke (PLoS ONE, 2026)
Science has provided insight into the physical signs of animal abuse, such as the presence of fractures in different healing stages. Possible behavioural signs of animal abuse are understudied. In studies on child abuse, behavioural signs have been identified. We aimed to study if similar signs would be viewed as relevant signs of animal abuse, focussing on physical abuse of cats and dogs. We targeted shelter staff and shelter animal adopters, as these people may come in contact with abused animals, are known to be willing to participate in research and may do so without ethical constraints applying. We found that the behavioural signs based on child abuse studies, were deemed relevant for the assessment of animal abuse by the respondents in our small-scale study (N = 23 shelter staff and N = 132 shelter animal adopters). Behavioural signs of fear, such as fear of the owner, were deemed most relevant. Person-specific fear was indicated by shelter staff and shelter animal adopters as a more accurate indicator of animal abuse than aggression, problems with human-social bond formation and person-specific pleasing behaviour. This study held a limited number of respondents, but indicates a possible use of behavioural signs in studying animal abuse. To further assess the validity of animal behavioural signs as a source of animal abuse recognition, future studies will need to observe animals known to have previously suffered abuse. These studies should aim to use ethograms that include objective descriptions of behaviours that may be of interest to animal abuse experiences. Our study indicates that shelter animal staff and adopters may differ in their appraisal of behaviours other than fear, when assessing a likeliness of animal abuse. Studying such differences in larger samples may provide insight into how these populations assess an animal’s possible abuse experience or lack thereof.